Pelatihan Design Graph Mobile: Upaya Peningkatan Kreativitas Siswa dalam Pembelajaran Di Masa Pandemi - Hulaikah, Mifta; Zulianto, Aris; Syaifudin, Ahmat Arif (Dinamis: Jurnal Pengabdian Kepada Masyarakat, 2021)
The pandemic changed the student learning process at the basic education level, from face-toface and turned into an online system. It has resulted in one aspect of student skills, namely creativity, being not optimal developed. The mobile graphic design training program, use the pixel lab application, provides a stimulus for students to hone creativity through making designs that will be needed in doing school assignments. The method of this program is divided into three stages, situation analysis, needing analysis, and implementation. The training was attended by 30 students from MI Jatigede – Bojonegoro. The training is divided into three sessions: introduction the applications, guided practice, and self-paced assignments.